Pengaruh Corporate Governance terhadap Kualitas Laba pada Perusahaan Minyak dan Gas: Systematic Literature Review - Salwa Nabilah Putri; Rina Tjandrakirana DP (CV. ITTC INDONESIA, 2026)
The oil and gas industry is a strategic sector characterized by high risk, which may encourage earnings management practices and reduce the quality of financial reporting. Therefore, corporate governance plays a crucial role in enhancing transparency and earnings quality. Using a Systematic Literature Review (SLR) approach on 20 articles sourced from Google Scholar, Garuda, SINTA, and Scopus, this study aims to evaluate the effect of corporate governance on earnings quality. The findings indicate that corporate governance generally improves earnings quality by enabling better monitoring and control of management. However, the impact is not always consistent, as it is influenced by the effectiveness of governance implementation and firm-specific characteristics. This study highlights the importance of implementing good corporate governance to enhance the credibility of financial statements.